Contoh Penerapan Penetapan Zona Ekonomi Eksklusif: (Studi Kasus Imajiner Amalea v. Ritania atas Malachi Gap) - Misbachul Munir; Churun Ain Nabila Elsyam; Fazal Akmal Musyarri; Nenny Sihotang; Puput Brenda Afriyanti; Zipora Nadya A. Siregar (Jurnal Hukum Lex Generalis, 2020)
The Law of the Sea divides a country's maritime territorial boundaries into sections, one of which is the Exclusive Economic Zone or EEZ. EEZ is a maximum distance zone of 200 miles that can be utilized by resources but cannot be controlled by a country because for purposes such as shipping and flight navigation that are required in general. But because of the nature of its free use can trigger conflict between countries because it is like a domino that has a correlation with each other. In this paper will be spelled out examples of the application of EEZ conflict resolution in imaginary cases of the State of Amalea and the State of Ritania as a simulation of the settlement of EEZ determination based on unclos sea law 1982. This simulation has a dynamic of interesting fictitious facts in terms of law with a conventional settlement that is the consensus of the parties. Referring to UNCLOS 1982, the utilization of marine aspects needs to be considered so as not to interfere with other countries.